THE INFLUENCE OF SOAKING WATER EXCHANGE TIME AND COMMERCIAL FUNGAL DOSES TO RUBBER SEED (Havea brasilliensis Muell.Arg) TEMPEH QUALITY - Novita, Maria Renika (Jurnal Sains Pertanian Equator, 2019)
This study aims determine the influence of soaking water exchange time and commercial fungal doses to rubber seed tempeh. This research used randomize block design (RBD) 2 factorial combination were (1) soaking water exchange time 6, 9 and 12 hour, and (2) combination fungal doses 0,01, 0,1 dan 1 %(b/b.) Observation parameters to be measured content of, ash, protein, fat, carbohydrate, and HCN. Result were analyzed with Anova and BNJ 5% level test. The results of the study showed a combination of soaking water exchange time 12 hour and commercial fungal doses 1% the best treatment. Chemical characteristic of rubber seed werecontent water 54.2%, ash 1.01%, protein 27.51%, fat 16.31%, carbohydrate 3.75% and HCN 4.64 mg/L.